43rd AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2007
DOI: 10.2514/6.2007-5602
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fusion Engine

Abstract: A new concept for an interplanetary and interstellar missions is discussed, which is based on a compact spherical tokamak fusion reactor and can potentially revolutionize human space flights by providing safe and affordable in-space transportation. The goal of this paper is an assessment of the concept employing the recent advances in fusion research. This concept, in contrast to other fusion concepts, utilizes the natural drift motion of charged particles in order to create a directed flux of energetic partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The idea of using fusion power for spacecraft propulsion has a long history [11][12][13][14], with its support arising from the high energy density of the fuel and the high velocity of the fusion products. Early proponents of fusion rockets that provided steady propulsion based their designs on the fusion devices that are tokamaks [15,16], mirror machines [17] and levitated dipoles [18]. The experimental results of the early period in fusion history indicated that the plasma's anomalous transport, meaning poor plasma energy confinement, Deuterium-Tritium (D-T) burning, large and powerful machines, many meters in diameter, producing over a gigawatt in power and requiring a meter or more of neutron shielding.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of using fusion power for spacecraft propulsion has a long history [11][12][13][14], with its support arising from the high energy density of the fuel and the high velocity of the fusion products. Early proponents of fusion rockets that provided steady propulsion based their designs on the fusion devices that are tokamaks [15,16], mirror machines [17] and levitated dipoles [18]. The experimental results of the early period in fusion history indicated that the plasma's anomalous transport, meaning poor plasma energy confinement, Deuterium-Tritium (D-T) burning, large and powerful machines, many meters in diameter, producing over a gigawatt in power and requiring a meter or more of neutron shielding.…”
Section: Introductionmentioning
confidence: 99%